The forty rules of love - Shafak, Elif (London Penguin Books, 2015)
Discover the forty rules of love ... Ella Rubinstein has a husband, three teenage children, and a pleasant home. Everything that should make her confident and fulfilled. Yet there is an emptiness at the heart of Ella's life - an emptiness once filled by love. So when Ella reads a manuscript about the thirteenth-century Sufi poet Rumi and Shams of Tabriz, and his forty rules of life and love, her world is turned upside down. She embarks on a journey to meet the mysterious author of this work. It is a quest infused with Sufi mysticism and verse, taking Ella and us into an exotic world where faith and love are heartbreakingly explored